Alienage Classifications and the Denial of Health Care to Dreamers - Fatma Marouf (Washington University Law Review, 2016)
In the Affordable Care Act (“ACA”), passed in 2010, Congress provided that only “lawfully present” individuals could obtain insurance through the Marketplaces established under the Act. Congress left it to the Department of Health and Human Services (“HHS”) to define who is “lawfully present.” Initially, HHS included all individuals with deferred action status, which is an authorized period of stay but not a legal status. After President Obama announced a new policy of Deferred Action for Childhood Arrivals (“DACA”) in June 2012, however, HHS amended its regulation specifically to exclude DACA recipients from the definition of “lawfully present.” The revised regulation denied DREAMers—undocumented immigrants brought to the United States as children—access to affordable health care, while providing it to similarly situated individuals who had been granted deferred action through other means. This Article examines whether the exclusion of DREAMers from the ACA violates equal protection principles, highlighting critical inconsistencies and gaps in the case law on standards of review for alienage classifications. A circuit split exists about whether non-legal permanent residents are ever entitled to strict scrutiny, and the extent of the Executive’s power over immigration remains unclear, as does the allocation of power within the executive branch. In addition, courts are divided about the standard of review that applies when states discriminate against noncitizens pursuant to a federal statute. All of these issues complicate the analysis and underscore the need to reevaluate an unraveling tiered approach to judicial review.
Keywords: health law; health care; Affordable Care Act; ACA; DACA; Deferred Action for Childhood Arrivals; dreamers; Dream Act; immigration